Pengaruh Pendidikan Kewirausahaan, Self Efficacy, Locus of Control dan Adversity Intelligence Terhadap Minat Berwirausaha : (Studi pada Siswa SMK di Soloraya) - Yoppi Syahrial; Indri Sri Endarwati; Rohana Wanaswati; Elma Putri Utami (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The problem currently facing Indonesia is unemployment which continues to increase due to limited job opportunities. One thing that can be done to overcome this is by providing entrepreneurial activities. This research is to explore problems regarding factors that can influence interest in entrepreneurship among vocational school students in Soloraya, namely Entrepreneurship Education, Self-efficacy, Advertising Intelligence & Locus of Control. This research aims to establish the theory of planned behavior, especially to explain the role of self-efficacy, adversity intelligence & interest in entrepreneurship. This research involved 316 vocational school students studying in Soloraya which showed that entrepreneurship education, adversity intelligence and locus of control had no effect on interest in entrepreneurship. Meanwhile, self-efficacy is able to influence students' interest in entrepreneurship in vocational schools throughout Solo Raya. This research was tested using the smart PLS analysis.